Pendampingan Penggunaan Aplikasi Cinta Qur’an Pada Program Ngaji Gaul Dalam Kuliah Pengabdian Masyarakat (KPM) DI TPQ As-Syifa Dusun Kemloko, Desa Bumiayu, Kecamatan Selopampang, Kabupaten Temanggung - Alifa Noor Azzah; Wafa Nur Nadila; Wafiq Azizah; Dwi Riski Suandi; Laili Ermawati; Syahrul Ardiansyah; Madarina Rosyqoh; Lutfiah Al Kharimah; Novan Syahrurromadhon; Rahmatia Hirda Al Husna; Iyan Almas Albantani; Indra Cahyo Maulana; Muhammad Ibnu Nabil; Ahmad Robihan (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
This assistance aims to build a positive image of religious activities, especially learning the Qur'an, able to present a relaxed, contemporary, easy-to-remember approach, and effective in attracting interest and reducing dependence on gadgets that plunge into bad things. This assistance was carried out at TPQ As-Syifa Kemloko Hamlet, Bumiayu Village by utilizing the "Love Al-Qur'an" application. This application is used to assist teachers in the teaching process and as a support for the use of technology in the "Reciting Slang" program. This assistance uses a demonstration approach for its data collection techniques, namely by direct observation, interviews with teachers, students and women as well as documentation related to the use of the "Love Al-Qur’an" application. The results of this assistance obtained information that the use of the "Love Al-Qur’an" application can make it easier for teachers to provide material about learning the Qur'an in a fun way. As for students and women, the use of the "Cinta Qur'an" application can help them memorize the Qur'an easily and are willing to apply this application in their daily lives. However, in the use of the "Love Al-Qur’an" application, there are also limitations in the use of gadgets because they are not personal property but belong to parents so that there is no maximization of students and women in the use of this application.